PENDAMPINGAN PEMAHAMAN KONSEP MATEMATIKA DAN KEPERCAYAAN DIRI ANAK BERKEBUTUHAN KHUSUS DI KOTA MADIUN - Ariyanti, Gregoria; Easti Rahayu Maya Sari, Ana; Ary Wicaksono, David (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2021)
The government, through the Ministry of National Education, especially through the Directorate General of Higher Education, has begun to facilitate the development or education of children with special needs. Likewise, children with special needs are provided with other simple scientific knowledge, including Mathematics. There is a tendency for teachers who are accustomed to thinking that the learning process is just an attempt by the teacher to enter the cognitive realm of their students. Learning media for children with special needs are applied in this service activity. Technology in the form of special mathematics teaching aids for children with special needs aims to make children have better abilities and can increase their self-confidence. Children with special needs who turn out to have progressed in knowledge, for example, numbers and counting in simple mathematics, will feel happy and their confidence will eventually emerge. For this, it is necessary to strive for pleasant learning conditions equipped with learning aids and assistance in understanding simple Mathematics concepts, so that confidence in the child will slowly emerge. Based on the above background, community service activities are carried out. The service method is in the form of assistance in understanding mathematical concepts and self-confidence for children with special needs. The subjects of this community service activity were students of SLB Bhakti Luhur in Manguharjo District, Madiun City. Meanwhile, the purpose of this service activity is to improve the ability to understand simple mathematical concepts that are fun for children with special needs and increase the self-confidence of children with special needs. The results of the implementation of the service show an increase in the ability to understand simple mathematics and increase the self-confidence of children with special needs. --- Pemerintah melalui Departemen Pendidikan Nasional khususnya melalui Direktorat Jenderal Pendidikan Tinggi, mulai memfasilitasi perkembangan atau pendidikan anak berkebutuhan khusus. Demikian juga, anak berkebutuhan khusus dibekali pengetahuan ilmu sederhana yang lain, diantaranya Matematika. Adanya kecenderungan guru yang terbiasa menganggap bahwa proses belajar itu hanyalah upaya guru memasuki ranah kognitif siswanya. Media pembelajaran bagi anak berkebutuhan khusus diterapkan dalam kegiatan pengabdian ini. Teknologi berupa alat peraga Matematika khusus bagi anak berkebutuhan khusus, bertujuan agar anak memiliki kemampuan yang lebih baik dan dapat menambah kepercayaan diri mereka. Anak berkebutuhan khusus yang ternyata memiliki kemajuan dalam pengetahuan, misalnya bilangan dan berhitung dalam Matematika sederhana, akan merasa senang dan kepercayaan dirinya lama kelamaan akan muncul. Untuk hal tersebut, maka perlu diupayakan kondisi belajar yang menyenangkan dengan dilengkapi alat bantu belajar dan pendampingan pemahaman konsep Matematika sederhana, sehingga akan muncul perlahan-lahan kepercayaan diri pada anak tersebut. Berdasarkan latar belakang di atas, maka dilakukan kegiatan pengabdian kepada masyarakat. Metode pengabdian berupa pendampingan pemahaman konsep matematika dan kepercayaan diri bagi anak berkebutuhan khusus. Subjek dari kegiatan pengabdian kepada masyarakat ini adalah siswa SLB Bhakti Luhur di Kecamatan Manguharjo kota Madiun. Sedangkan, tujuan dalam kegiatan pengabdian ini adalah meningkatkan kemampuan pemahaman konsep matematika sederhana yang menyenangkan bagi anak berkebutuhan khusus dan meningkatkan kepercayaan diri anak berkebutuhan khusus. Hasil pelaksanaan pengabdian menunjukkan adanya peningkatan kemampuan pemahaman matematika sederhana dan peningkatan kepercayaan diri anak berkebutuhan khusus.